2024
DOI: 10.1002/mdc3.13977
|View full text |Cite
|
Sign up to set email alerts
|

What are the Key Phenomenological Clues to Diagnose Functional Tic‐Like Behaviors in the Pandemic Era?

Christelle Nilles,
Davide Martino,
Lindsay Berg
et al.

Abstract: BackgroundFunctional tic‐like behaviors (FTLBs) can be difficult to distinguish from tics.ObjectivesTo describe the phenomenology of FTLBs in youth and assess the movements and vocalizations most suggestive of the diagnosis.MethodsWe compared the phenomenology of tics between youth (<20 yr) with FTLBs and with primary tics from our Registry in Calgary, Canada.ResultsTwo hundred and thirty‐six youths were included: 195 with primary tics (75% males; mean age: 10.8 yr) and 41 with FTLBs (98% females; 16.1 yr).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The timeframe of the studies spans four years (between 2021 and 2024), and the geographic distribution is skewed towards North America, where the majority of the studies took place. Specifically, five studies were conducted in Canada [ 32 , 33 , 39 , 41 , 42 ], two each in Germany [ 31 , 40 ] and in the United States [ 35 , 37 ], and one each in Australia [ 34 ], Denmark [ 36 ], and the United Kingdom [ 38 ]. All studies were conducted within specialist clinic settings.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The timeframe of the studies spans four years (between 2021 and 2024), and the geographic distribution is skewed towards North America, where the majority of the studies took place. Specifically, five studies were conducted in Canada [ 32 , 33 , 39 , 41 , 42 ], two each in Germany [ 31 , 40 ] and in the United States [ 35 , 37 ], and one each in Australia [ 34 ], Denmark [ 36 ], and the United Kingdom [ 38 ]. All studies were conducted within specialist clinic settings.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar study conducted on a German sample ( n = 32), half of the patients with functional tic-like behaviors were males and were not more likely to present with co-morbid anxiety and depression than patients with neurodevelopmental tics [ 40 ]. Finally, three studies were recently conducted at the same specialist clinic in Canada on 35 [ 39 ], 40 [ 42 ], and 41 [ 41 ] adolescents and young adults with functional tic-like behaviors, respectively. In addition to confirming a significantly higher proportion of females with older age at symptom onset, these studies found that patients with functional tic-like behaviors were more likely to present with anxiety and depression [ 39 ], to be gender-diverse individuals [ 42 ], and to report coprophenomena, popping, whistling, simple head movements, and self-injurious behaviors [ 41 ] than patients with neurodevelopmental tics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations